2020
DOI: 10.1097/md.0000000000021052
|View full text |Cite
|
Sign up to set email alerts
|

A correlation study of emergency department nurses’ fatigue, perceived stress, social support and self-efficacy in grade III A hospitals of Xi’an

et al.

Abstract: Fatigue is a universal and challenging problem in a nurse's career, particularly for those working in the emergency department. Through analyzing the current status of emergency department nurses’ fatigue, the purpose of this study is to provide guidance for occupational health promotion strategies making and fatigue relief. Cross-sectional study was conducted among nurses working in emergency department in 6 grade III A hospitals in Xi’an, China. Convenience sample of 346 nurses agreed to participa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
8
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 42 publications
7
8
1
3
Order By: Relevance
“…In many of the domains of stress studied (almost all areas of work changes and burden, lack of resources, and personal influence), the level of stress was higher among the nurses, which parallels previous studies [17,18]. Studies have shown that even when not in pandemic situations, nurses working in the ED encounter high levels of fatigue and stress, and this has a great effect on self-efficacy [6]. Many studies in the COVID-19 pandemic era, as well as the SARS epidemic era, have also indicated that nurses experience high levels of stress including those that are work-related, health concerns, and social isolation, and thus require intervention [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
“…In many of the domains of stress studied (almost all areas of work changes and burden, lack of resources, and personal influence), the level of stress was higher among the nurses, which parallels previous studies [17,18]. Studies have shown that even when not in pandemic situations, nurses working in the ED encounter high levels of fatigue and stress, and this has a great effect on self-efficacy [6]. Many studies in the COVID-19 pandemic era, as well as the SARS epidemic era, have also indicated that nurses experience high levels of stress including those that are work-related, health concerns, and social isolation, and thus require intervention [19][20][21].…”
Section: Discussionsupporting
confidence: 83%
“…In addition, the clients, who referred to nurses, have predominantly acute and special situations and sometimes are overcrowded in the emergency department at the times of chain accidents and similar cases, which lead to more stress in nurses (40,43). According to a study by Oliveira et al nurses experienced a higher workload than other occupational groups, which was more related to poor working conditions and to a lack of job satisfaction (44).…”
Section: Discussion the Present Situation Of Mental Workload Job Satisfactionmentioning
confidence: 99%
“…Aunque dicha modalidad se implementó para evitar las pérdidas masivas de empleo (6,7,8,9) , a su vez produjo consecuencias negativas como la sobrecarga, el estrés y la confusión emocional (18,19) . Así mismo, impactó en las dinámicas familiares, los hábitos de sueño y las rutinas de alimentación de las personas (16,17) , lo que generó afectaciones a nivel físico (dolores o lesiones músculo -esqueléticas) (16,17) y psicológico (estrés, ansiedad, irritabilidad) aspectos que derivaron fatiga laboral (22,23,24) . Aunque las investigaciones acerca de esta temática se encuentran en auge por la novedad e importancia que tiene en el ámbito laboral, en su mayoría se ha optado por investigaciones monográficas o de revisión bibliográfica, dejando un poco de lado el indagar el impacto que ha tenido en el diario vivir de los colaboradores.…”
Section: Discussionunclassified
“…De acuerdo con lo encontrado en el estudio, los participantes presentaron fatiga laboral, la cual se caracterizó por la manifestación de síntomas asociados a la carga física, tales como cansancio, malestar en alguna parte del cuerpo, pesadez o fatiga visual y entumecimiento de las articulaciones (34) . Así mismo, indicaron que, respecto a la carga mental y los efectos psicofisiológicos, experimentaron sintomatología relacionada con capacidad mental disminuida, somnolencia, irritabilidad, y apatía, así como, estado de ánimo decaído, agotamiento (cansancio, estrés, aburrimiento), palpitaciones y dificultad para respirar (22,23,25,26) . Lo anterior concuerda con diferentes autores que afirman que la fatiga laboral se encuentra relacionada con las variables propias de la carga mental (20) y física (37) , dado que, cuando el trabajador realiza un sobreesfuerzo cognitivo al tener que procesar una gran cantidad de información (20) y/o se encuentra expuesto a algún tipo de tensión (estática, repetitiva o excesiva) por un largo periodo de tiempo (37) , surgen afectaciones como las anteriormente mencionadas que impactan de manera negativa en el bienestar del colaborador (35) .…”
Section: Discussionunclassified
See 1 more Smart Citation